PHOTOMETRICAL STUDY OF SU UMA-TYPE BINARY RZ LMI DURING THE SUPEROUTBURST IN 2001 - Baklanov, A. V.; Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
We perform the photometry of the SU UMa-type binary, RZ LMi during the superoutburst in 2001. The star displayed the superoutburst decay with a rate ∼ 0.m07/day. We detected the superhumps with an amplitude up to 0.m2. Some of the superhumps show the eclipse-like feature. The ephemeris for maxima is HJD= 2451933.5939(6) + 0.059296(40) · E.